Sex, but not skin tone affects penetration of red‐light (660 nm) through sites susceptible to sports injury in lean live and cadaveric tissues. Issue 7 (1st April 2019) - Hu, Di; van Zeyl, Marc; Valter, Krisztina; Potas, Jason R.
Abstract : Red‐light treatment is emerging as a novel therapy for promoting tissue recovery but data on red‐light penetration through human tissues are lacking. We aimed to: (1) determine the effect of light irradiance, tissue thickness, skin tone, sex and bone/muscle content on 660 nm light penetration through common sites of sports injuries, and (2) establish if cadaver tissues serve as a useful model for predicting red‐light penetration in live tissues. Live and cadaver human tissues were exposed to 660 nm light at locations across the skull, spinal cord and upper and lower limbs. Red‐light was produced by a light emitting diode array of various irradiances (15‐500 mW/cm 2 ) and measured by a light‐probe positioned on the tissue surface opposite to the light emitting diodes. 100 mW/cm 2 successfully penetrated tissue <50 mm thick; a disproportionate irradiance increase was required to achieve deeper penetration. Penetration was unaffected by skin tone, increased with irradiance and relative bone/muscle composition, and decreased with greater tissue thickness and in males. Live and cadaveric tissue penetration did not differ statistically for tissues <50 mm but cadavers required more red‐light to penetrate >50 mm. These results assist clinicians and researchers in determining red‐light treatment intensities for penetrating human tissues. Abstract : Red‐light penetrates the skin and improves functional outcomes following injury of various tissues, including the brain, spinal cord, muscles, tendons and joints. This study quantifies how much red‐light penetrates human tissues and will aid clinicians and researchers in determining what intensities are required to conduct their work. The photo shows 100 mW/cm 2 of red‐light passing through the hands of a light skin‐toned male (left) and dark skin‐toned female.